Bandwidth-Oriented Motion Estimation Algorithm For Real Time Mobile Video Application (International Journal of Engineering and Computer Science, 2013)
Resource-limited systems such as mobile video applications, the available memory bandwidth is dynamically changing and are limited.This project proposes a data bandwidth-oriented motion estimation(ME) design for resource-limited mobile video applications.An integrated bandwidth rate distortion optimization framework is used.This framework predicts and allocates the appropriate data bandwidth for motion estimation under a limited bandwidth supply.The residue number system is used in these framework in order to provide low power consumption and high scalability data bandwidth oriented ME